Review on Financial Sector Assessment Program (FSAP) and its Adoption of Proposed Islamic Financial Sector Assessment Program (IFSAP) - Muchammad Taufiq Affandi (University of Darussalam Gontor, 2019)
The Financial Sector Assessment Program (FSAP) states that a sound and well-functioning financial system is supported by three pillars to sustain orderly financial development and stability which relate to the macroeconomic factors, regulatory and supervisory framework, and the infrastructures. There is an urgency to review to what extent FSAP has adopted Proposed Islamic Financial Sector Assessment Program (IFSAP) Template. This note will try to review the FSAP on some selected countries and analyse the influence of proposed IFSAP to the FSAP. Result of this review shows that, based on 2013 data, the IMF-World Bank has adopted in a limited way the proposed template by IRTI-IDB. Overall, there is a very limited significance of change in the of FSAP model.